The Influence of Internal Consistency Level in ‎Comparative Judgments on Data Fit to ‎Thurston’s Law of Comparative Judgments - Al-Momani ‎, Nisrein; Sawalmeh, Yousef (Jordan Journal of Educational Sciences, 2024)
The study aimed to examine the internal consistency values of a set of judgments and assess the effect of judgment consistency on the conformity of the data in the fifth case of Thurston’s law of comparative judgments. The study included 402 science instructors from schools in both Irbid and Bani Obeid districts who completed an electronic survey. The survey, in its final revision, comprised seven different types of instructional tools employed in science education, given in 21 pairings. Participants had to determine which of the two stimuli held greater significance in the context of science instruction. The findings showed a disparity in the consistency of the internal coefficient values among the arbitrators. The findings further indicated that the level of internal consistency has an effect on the compatibility of the data in the fifth case of Thurston’s Law of Comparative Judgments. The probability of data fitting improves as the level of internal consistency increases